Insights into the naphthalenide-driven synthesis and reactivity of zerovalent iron nanoparticles. Issue 44 (4th November 2021) - Reiß, Andreas; Donsbach, Carsten; Feldmann, Claus
Abstract : The thermal and chemical stability of [LiNaph]/[NaNaph] is examined. The most stable [LiNaph] in THF is used to obtain Fe(0) nanoparticles, which themselves serve as a starting material to obtain new iron coordination compounds. Abstract : The chemical and thermal stability of alkali metal naphthalenides as powerful reducing agents are examined, including the type of alkali metal ([LiNaph] and [NaNaph]), the type of solvent (THF, DME), the temperature (−30 to +50 °C), and the time of storage (0 to 12 hours). The stability and concentration of [LiNaph]/[NaNaph] are quantified via UV-Vis spectroscopy and the Lambert–Beer law. As a result, the solutions of [LiNaph] in THF at low temperature turn out to be most stable. The decomposition can be related to a reductive polymerization of the solvent. The most stable [LiNaph] solutions in THF are exemplarily used to prepare reactive zerovalent iron nanoparticles, 2.3 ± 0.3 nm in size, by reduction of FeCl3 in THF. Finally, the influence of [LiNaph] and/or remains of the starting materials and solvents upon controlled oxidation of the as-prepared Fe(0) nanoparticles with iodine in the presence of selected ligands is evaluated and results in four novel, single-crystalline iron compounds ([FeI2 (MeOH)2 ], ([MePPh3 ][FeI3 (Ph3 P)])4 ·PPh3 ·6C7 H8, [FeI2 (PPh3 )2 ], and [FeI2 (18-crown-6)]). Accordingly, reactive Fe(0) nanoparticles can be obtained in the liquid phase via [LiNaph]-driven reduction and instantaneously reacted to give new compounds without remains of the initial reduction ( e.g. LiCl, naphthalene, and THF).